Pengaruh Karakteristik Individu, Komitmen Organisasi dan Dukungan Organisasi Terhadap Kinerja Pegawai pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Bima - Indra Juniawan; Firmansyah Kusumayadi; Rahmatia Rahmatia (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the influence of individual characteristics, organizational commitment, and organizational support on employee performance at the Public Works and Spatial Planning Office of Bima Regency. This research employed an associative research design with a quantitative approach. The population consisted of 202 employees, while the sample comprised 90 civil servants selected using a purposive sampling technique. Data were collected through a questionnaire using a Likert scale. The data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient test (R), coefficient of determination test (R²), partial significance test (t-test), and simultaneous significance test (F-test) using SPSS version 26. The results showed that, partially, individual characteristics had a positive and significant effect on employee performance, with a significance value of 0.000 < 0.05. Organizational commitment also had a positive and significant effect on employee performance, with a significance value of 0.000 < 0.05. Meanwhile, organizational support did not have a significant effect on employee performance, with a significance value of 0.145 > 0.05. Simultaneously, individual characteristics, organizational commitment, and organizational support had a significant effect on employee performance, as indicated by the F-test significance value of 0.000 < 0.05. The coefficient of determination (R²) was 0.626, indicating that 62.6% of the variation in employee performance could be explained by the three independent variables, while the remaining 37.4% was influenced by other factors not examined in this study.